Western Imperialism Against the Islamic World - Robiatul Samiah; Lina Pusvisvasari; Agna Rahmat Maulana; Sarah Apiani (al-Wadhih: Journal of Islamic History and Civilization, 2025)
Western imperialism in the Islamic world is a pivotal chapter in the study of Islamic Civilization History, demonstrating how the dominance of European colonial powers transformed the political, economic, social, and cultural landscape of the Islamic world. This phenomenon intensified in the 18th century, coinciding with the decline of Islamic powers such as the Ottoman Empire, Mughal Empire, and Safavid Dynasty, alongside the rising influence of European nations like Britain, France, and the Netherlands. This imperialism was not only executed through military expansion but also through economic infiltration, manipulative diplomacy, and the dissemination of modernity ideologies that often disrupted traditional Islamic order. Its impact was far-reaching, encompassing political disintegration due to colonial divisions, the exploitation of natural resources that drained the Islamic world's wealth, and the marginalization of Islamic culture and religion under the narrative of Western superiority. Colonial-introduced education systems, laws, and administration often displaced traditional Islamic values, creating identity conflicts among Muslims. However, amidst this dominance, various forms of resistance emerged, both physically through jihad and nationalist movements, and intellectually through Islamic reform spearheaded by figures such as Jamaluddin Al-Afghani, Muhammad Abduh, and Rashid Rida. This study seeks to explain how Western imperialism influenced the historical trajectory of Islamic civilization, both in colonial and post-colonial contexts. This analysis encompasses critical aspects such as colonial strategies, Islamic world responses, and long-term impacts that are still felt in the modern era. With a historical-critical approach, this abstract aims to provide a profound perspective on how Western imperialism not only posed a challenge to the Islamic world but also acted as a catalyst for the resurgence of Islamic identity and civilization amidst globalization.